Covid-Prev Observatory: Contribution to Transparency and Accountability in Public Management in Times of Pandemic - Lima, Diana Vaz de (2021)
The Covid-19 pandemic and its countermeasures have brought pressures on social and welfare assistance. Along with this, come the challenges of information being dispersed and complex, susceptible to distortions, and a society with distinct capacities for assimilation and analysis. This paper aims to present the experience of the Covid-Prev Observatory as a tool for transparency and accountability in the public management of social security in times of pandemic. This experience with the social observatory has encompassed the choice of themes and variables to be disseminated and analyzed, the visual planning and dissemination strategy, and the discussion of the observatory's role and potential. Thus, a multidisciplinary team has developed a project aiming to analyze the impact of Covid-19 on the Brazilian Social Security System, from different perspectives, both with the reproduction of data and information, and for the elaboration of analyses: impacts of the pandemic on the labor market and its effects on the evolution of social security revenues and expenses, effects of the pandemic on vulnerable groups, sustainability of pension funds, impacts on the financial market, among others. This information was first disclosed on the Blogger platform, and then on an electronic website whose disclosure was made both on the social networks of the research participants themselves and on the social networks of entities interested in the topic, such as the Brazilian Association of State and Municipal Pension Institutions (ABIPEM). In its short period of existence, the observatory has obtained more than 10 thousand accesses, either from Brazil and other countries. The observatory has presented data and analyses in a simple way, based on scattered information with different levels of complexity. In these analyses, the aim has been to establish relationships between facts correlated to social security and welfare. Thus, it is understood that the observatory has collaborated as a transparency and accountability tool with respect to the theme of social security in Brazil, serving as a discussion of the challenges and potentialities of social observatories.